The research methodology for assessing prophetic food consumption among lactating mothers - Mohd Shukri, Nor Azwani; Muhammad, NO; Khattak, Muhammad Muzaffar Ali Khan; Muhammad, I; Abdul Ghani, Radiah; AB, Siti Munirah (2016)
Introduction: The phrase ‘Prophetic food and medicine’ reflects the words and actions of the Holy Prophet Muhammad (PBUH) with bearing of disease, treatment of disease, and care of patients. Among plants mentioned in the Al-Quran, Al-Hadith and Islamic literature are dates, pomegranates, figs, olive and black cumin seeds. These plants are widely used for medicinal purposes, as functional foods and industrial products. However, there are limited studies found on their effect on human milk quality and quantity. The objective is to describe the methodology to assess the knowledge, attitude, and practice regarding prophetic foods consumption among lactating mothers. Methodology: Pregnant Malay mothers aged 18 to 40 years old, at gestational age 32 weeks and above will be recruited. During the lactation period, their dietary intake (specifically the consumption of prophetic foods) will be assessed using a quantitative method which is food frequency questionnaire. A subsample of mothers will then be interviewed using semi-structured interview method on the prophetic food consumption. Quantitative and qualitative data will be analysed using SPSS and NVivo softwares, respectively. Result: Reports of positive effects of prophetic food consumption on lactation experience such as improving human milk production is anticipated from this study. In addition, it will provide a foundation for further exploration on the role of prophetic food consumption in the lactation process. Conclusion: This research is at the forefront to provide the data on potential practice and application of prophetic foods to positively influence lactation experience and quality of human milk.